Movable Automatic Car Wash Truck - Farshad Amirjani; Seyed Ali Akbar Mousavi; Shahin Amirjani; Mahmood Karimi (Management Department Universitas Islam Negeri Sumatera Utara, 2022)
In this project, we intend to design and build a movable/mobile car wash mounted on a truck and inside a container. Upon exiting the container, parked cars can be washed on the spot, anywhere and anytime. There will no longer be a need for drivers to waste their precious time in ordinary car washes Because, most office workers are on the job 8 hours a day and do not have sufficient free time to drive to a traditional or automatic car wash. Moreover, it is difficult and challenging to wash the car in unfavorable weather. This is a completely novel project.Keywords: Ability to be folded and placed in a container, car wash businesses, two distinct models (with & without brush)